Renegosiasi Otoritas Lintas Generasi: Tinjauan Sistematis Ancaman Identitas Pemimpin Milenial di Tengah Eskalasi Generasi Z - Devia Alwasy Maulida; Naela Syifaul Bariyah; Fauzi Nurrokhim (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study aims to analyze the perspective of Millennials and older generations toward the phenomenon of Generation Z power dominance in modern organizational ecosystems through a Systematic Literature Review (SLR) approach. The SLR method based on the PRISMA 2020 protocol enabled the systematic identification and synthesis of 24 scientific articles published between 2021 and 2025 from six international academic databases. The findings identified three main themes emerging from the literature: (1) the shift in power distribution influenced by Generation Z's digital competencies and new values; (2) the psychological and behavioral responses of Millennials, including leadership identity tensions and managerial strategy adaptations; and (3) the urgency of developing integrative cross-generational leadership approaches. These findings contribute to the development of multigenerational leadership theory in the context of post-disruption industrial and organizational psychology, while also proposing a practical framework for organizations in managing intergenerational authority transitions constructively.